2019
DOI: 10.1016/j.cnp.2019.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular ultrasound in clinical practice: A review

Abstract: HighlightsNeuromuscular ultrasound (NMUS) augments clinicians’ diagnostic capabilities.NMUS requires a basic understanding of ultrasound technology and relevant anatomy.Uses include evaluation of neuropathies, myopathies, and motor neuron diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 114 publications
(159 reference statements)
1
65
0
Order By: Relevance
“…At rst, QMUS is only suited for displaying super cial muscle layers, the reference values cannot set up reliably for deeper muscles. The second, QMUS cannot distinguish the abnormal signal intensities because of in ammation, brosis, or fatty in ltration [15]. Composite biomarkers, QMUS and impedance electromyography, may provide a more effective means for tracking the disease progression and therapeutic responses of DMD [16].…”
Section: Discussionmentioning
confidence: 99%
“…At rst, QMUS is only suited for displaying super cial muscle layers, the reference values cannot set up reliably for deeper muscles. The second, QMUS cannot distinguish the abnormal signal intensities because of in ammation, brosis, or fatty in ltration [15]. Composite biomarkers, QMUS and impedance electromyography, may provide a more effective means for tracking the disease progression and therapeutic responses of DMD [16].…”
Section: Discussionmentioning
confidence: 99%
“…In compressive neuropathies, localised enlargement, just proximal to the site of compression, decreased echogenicity, loss of the internal fascicular structure and increased blood flow, can all be commonly observed[ 3 , 65 ]. However, a maximum point of enlargement should be identified along the course proximal and distal to the site of compression, as enlargement can be present distal to the entrapment site, and nerve mobility may alter the positioning of such enlargements[ 66 ]. The entrapment site may display an hour-glass or spindle-shaped appearance in longitudinal views[ 66 ].…”
Section: Us Appearances In Peripheral Nerve Disordersmentioning
confidence: 99%
“…However, a maximum point of enlargement should be identified along the course proximal and distal to the site of compression, as enlargement can be present distal to the entrapment site, and nerve mobility may alter the positioning of such enlargements[ 66 ]. The entrapment site may display an hour-glass or spindle-shaped appearance in longitudinal views[ 66 ]. Strictures, ganglion cysts, tumours, thrombosed arteries and other extrinsically or intrinsically compressive lesions can be identified by US as the cause of symptomatology, and hence can drastically alter the management paradigm.…”
Section: Us Appearances In Peripheral Nerve Disordersmentioning
confidence: 99%
“…Previous studies have shown that muscle ultrasound can differentiate between neuropathy and myopathy [6]. Moreover, Adler et al .…”
Section: Figurementioning
confidence: 99%
“…Previous studies have shown that muscle ultrasound can differentiate between neuropathy and myopathy [6]. Moreover, Adler et al described a target-like appearance, with increased central echogenicity and peripheral sparing of examined muscles on ultrasound in patients with GNE myopathy [7].…”
mentioning
confidence: 99%